Tinjauan Yuridis Pembubaran Organisasi Kemasyarakatan - Bambang Ariyanto (Faculty of Law Hang Tuah University, 2015)
Law No. 8 of 1985 only recognizes two forms of legal entity for the social organizations i.e. associations and foundations; while pursuant to Law No. 17 of 2013 on Social Organizations, there are four legal entity forms of the social organizations, namely (1) social organizations with legal entity of associations, (2) social organizations with legal entity of foundations, (3) social organizations with legal entity of foreign foundations, and (4) social organizations that are not legal entity. Four forms of the legal entity have different procedures for establishing, requirements, validating. The legal issue is whether the differences of the legal entity will affect the procedures for dissolving the organizations. Through normative research it is found that dissolving the organizations pursuant to Law No. 17 of 2013 is held through the legal procedures. The organizations may be dissolved by a binding court decision. The procedures for dissolving the organizations are also not simple. The first punishment is given as a written warning for three times. If it is ignored, then the punishment could be a suspension of grants, temporary suspension of the activity. The temporary suspension is conducted for 6 months and shall be permitted by the Supreme Court. If a verdict has permanently been published, a status of the legal entity can be revoked. The revocation is held within 30 days.